2019
DOI: 10.7759/cureus.5124
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrum of Hematological Disorders in Children with Pancytopenia Based on Bone Marrow Examination in a Tertiary Care Hospital

Abstract: IntroductionPancytopenia is a common presentation in the pediatric population. It is a manifestation of various diseases, and its etiology can be explained on the basis of bone marrow examination. The study aims to determine the etiological factors leading to pancytopenia via bone marrow examination in pediatric patients presenting in our hospital.Materials and methodsThis retrospective cross-sectional study was conducted in the Department of Pathology at a public sector tertiary care hospital. Data were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 4 publications
5
7
0
Order By: Relevance
“…12 Also similar study carried out by Vaidya et al found the most common age group was 21-30 years comprising 33.24 % of cases. 13 Similarly our results of age and sex ratio were comparable with other studies carried out by Thakkar et al, Manzoor et al, Yadav et al and Zeeshan et al [14][15][16][17] The study carried out by Lakhey et al in Nepal found weakness was the predominant presenting clinical feature in 73.9% cases. 18 Khodke et al studied 50 pancytopenia cases and found commonest presenting complaint was fever (40%) followed by weakness (30%) and bleeding manifestations (20%).…”
Section: Discussionsupporting
confidence: 90%
“…12 Also similar study carried out by Vaidya et al found the most common age group was 21-30 years comprising 33.24 % of cases. 13 Similarly our results of age and sex ratio were comparable with other studies carried out by Thakkar et al, Manzoor et al, Yadav et al and Zeeshan et al [14][15][16][17] The study carried out by Lakhey et al in Nepal found weakness was the predominant presenting clinical feature in 73.9% cases. 18 Khodke et al studied 50 pancytopenia cases and found commonest presenting complaint was fever (40%) followed by weakness (30%) and bleeding manifestations (20%).…”
Section: Discussionsupporting
confidence: 90%
“…[ 7 13 ] It can be observed from our study that megaloblastic anemia is a rare cause of pancytopenia in the pediatric age group, which is quite contrary to the study done by Zeeshan et al . [ 14 ] The incidence of kala-azar was 11.7% in the pediatric group in the study which makes it as the third leading cause of pancytopenia. The incidence of kala-azar is slightly higher than the study done by Naseem et al .…”
Section: Discussionmentioning
confidence: 97%
“…Pancytopenia is not a disease but a clinicopathological entity that can occur due to several disorders that primarily or secondarily affect the bone marrow [4]. Literature shows that pancytopenia affects nearly 3% to 5% of children; however, the data from developing countries regarding the etiological spectrum are scarce [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several infections including human immunodeficiency virus (HIV), miliary tuberculosis, leishmaniasis, and brucellosis can also cause pancytopenia among children [6][7][8]. Furthermore, some other factors like radiotherapy and chemotherapy can cause hypocellular bone marrow that leads to pancytopenia in children [5,9]. The spectrum of these etiologies is extremely varied and depends upon the geographical location, genetics, patient demographics, and nutritional profiles [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation